« Vu à la télé » : tourisme et fictions télévisuelles françaises - Marie-Hélène Chevrier; Isabelle Lefort (Bulletin de l’Association de Géographes Français)
As tourism linked to fiction in all its forms has developed strongly, national television productions have become important stimuli for domestic tourism. This is the case of contemporary French television series, both daily soaps (Plus belle la vie, Un si grand soleil, etc.) and crime series (Meurtres à..., Crimes en....) produced by the public service. This article sheds light on the transition in French television fiction from an interest in history (during the 1960s-1980s) to an interest in « territories ». They are now full-fledged agents in the fiction, even first in the writing of the scenarios (the place is chosen before the plot is elaborated), because the objectives are operations of promotion and territorial marketing. This study is based on the analysis of the crime series Meurtres à... co-produced by France 3 and RTBF since 2013. The fictionalization of the space of these « territories », their activities and their stories, tales and legends therefore participates in new geographical narratives, likely to be part of tourism practices as well as residential choices.